ANALISIS TINGKAT KESEJAHTERAAN RUMAH TANGGA PETANI KUBIS DI DESA TANJUNG KARI KECAMATAN PULAU BERINGIN KABUPATEN OGAN KOMERING ULU SELATAN (Program Studi Agribisnis Fakultas Pertanian Universitas Baturaja, 2021)
Revenue Analysis, and welfare level of cabbage farmer household in Tanjung Kari Village, Beringin Island, South OKU Regency. With a time of two months from September to November 2017. Sampling method used in this study is simple Random Sampling simple random method, specified is a particular sampling system at random and each has the same number of samples. With homogeneity of 1 Hectares land sample. The research method used in this research is survey method. The type of data used in this study includes primary data and secondary data. To analyze the level of welfare of Cabbage Household Households used Mathematical and Tabulation calculations with BPS Susenas (2014) indicator. Total Average Revenue of Cabbage Farmer's Family in Desa Tanjung Kari District of Beringin Island of South Ogan Komering Ulu Regency amounting to Rp 5,560,000 planting season, Average household expenditure of cabbage farmer in Tanjung Kari Village, Beringin Island, Ogan Komering Ulu Regency Rp 3,035,750 planting permits. Based on the results of the research, from the seven indicators of Central Bureau of Statistics 2014 the welfare level of household cabbage farmers in the village of Tanjung Kari District Beringin Island South Ogan Komering Ulu Regency including prosperous category as much as 90 percentKeywords : income, the risk, corn farming